2020
DOI: 10.3390/socsci9040051
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Loneliness from Where and What People Do

Abstract: The many devastating mental health outcomes associated with chronic loneliness is the motivation behind research into examining personal and demographic characteristics of the lonely. The present study sought to examine the connection of where people live (degree of urbanization) and what people do (leisure activities) with self-report of loneliness in a large sample (N = 8356) of unrelated Dutch adults. Information regarding where people live and what they do in their leisure time was entered into a regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…While online communication was seen as an effective medium for maintaining social interaction for some, many participants believed online forms of communication would be more isolating in the long‐term. These findings support Nowland et al ( 2018 , p. 71) contention that digital communication and social media technologies are most effective in reducing loneliness when enhancing existing relationships or forging new connections (i.e. the stimulation hypothesis) but are counterproductive when used as a substitute for real‐life physical interaction (the displacement hypothesis).…”
Section: Technology‐mediated Communication and Lonelinesssupporting
confidence: 82%
See 1 more Smart Citation
“…While online communication was seen as an effective medium for maintaining social interaction for some, many participants believed online forms of communication would be more isolating in the long‐term. These findings support Nowland et al ( 2018 , p. 71) contention that digital communication and social media technologies are most effective in reducing loneliness when enhancing existing relationships or forging new connections (i.e. the stimulation hypothesis) but are counterproductive when used as a substitute for real‐life physical interaction (the displacement hypothesis).…”
Section: Technology‐mediated Communication and Lonelinesssupporting
confidence: 82%
“…A rise in digital connectivity is being matched by a general social decline in physical face‐to‐face connections (Patulny, 2020 ) and this brings potential to induce feelings of emotional loneliness (Patulny, 2020 ). However, there are also noted positive effects of online communication when it ‘stimulates’ rather than ‘displaces’ offline contact (Nowland et al, 2018 ). This is particularly important in remote rural areas, found in many parts of Australia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An umbrella review of observational studies showed an association between loneliness and age (in a U-shaped way), female sex, low socioeconomic status and chronic medical conditions [ 6 ]. Recent research has confirmed the U-shaped or curvilinear association of loneliness with age, in that younger and much older individuals experience the most loneliness [ 7 ].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, loneliness is related to characteristics at the regional level, such as the degree of urbanization (MacDonald et al, 2020;Yan et al, 2014), population change (Buecker, Ebert, et al, 2020), and social inequality (Yan et al, 2014), which have changed worldwide over historical time, but at different rates depending on the country. All these historical changes may contribute to a better understanding of changes in emerging adults' loneliness over historical time.…”
Section: Technological Innovations and Other Structural Changesmentioning
confidence: 99%
“…The database is freely available and especially suited for our purposes as it contains nearly complete data on the environmental conditions of interest over the historical period examined in this meta-analysis. We used the regional-level population growth, degree of urbanization, and income inequality as spatiotemporal moderators in our analysis because these variables have been found to explain variance in loneliness in previous research (Buecker, Ebert, et al, 2020;MacDonald et al, 2020;Yan et al, 2014). Population growth was measured in annual percent, the degree of urbanization per nation was operationalized by the percent of the urban population of the total population, and the income inequality was indexed by the Gini coefficient.…”
Section: Moderator Analysesmentioning
confidence: 99%